Labor Income Share at the Firm Level: Global Trends - Saumik Paul; Hironobu Isaka (Institute of Labor Economics (IZA), 2019)
Micro-level studies provide insightful knowledge on the drivers of the labor income share. This paper introduces a novel firm-level dataset on the labor income share. Using the World Bank Enterprise Survey data, we put together an unbalanced panel comprising 146,666 firms from 139 countries and spanning a period from 2002 to 2017. We define the firm-level labor income share following three alternative approaches and compare these estimates across income groups, regions, firm sizes, and ownership types. The estimates average around .45, with considerable variations across regions and firm characteristics. Manufacturing firms tend to have a lower labor income share as the firm size increases. Large firms in services, both foreign and state-owned, pay a higher share of income to laborers. Regression results indicate that laborers in more productive firms enjoy a lower share of income; however, we do not find any strong correlation between globalization and the labor income share at the firm level.
Keywords: E24; E25; J30; 330; labor income share; cross-country data; income distribution